A parallel fractional explicit group modified AOR iterative method for solving fractional poisson equation with multi-core architecture - Syafiq, Nik Amir; Othman, Mohamed; Senu, Norazak; Ismail, Fudziah; Hamid, Nor Asilah Wati Abdul (Elsevier, 2024)
This research studies the Multi-core Architecture for the Modified Accelerated Overrelaxation (MAOR) scheme for solving the fractional Poisson equation. The equation is discretized using the fractional explicit group (FEG) finite difference method. This research also presents the parallel implementation of the fractional order iterative methods with the chessboard (CB) ordering strategies. The experimental results of the test problems were compared with other well known relaxation schemes to test their feasibility on parallel environment. The parameters that is measured include number of iteration, error, execution time and computational cost for various number of processors. © 2023 Elsevier Inc.